Longitudinal MRI in comparison to low-dose CT for follow-up of incidental pulmonary nodules in patients with COPD: a nationwide multicenter trial - Zhu, Lin; Li, Qian; Stackelberg, Oyunbileg von; Triphan, Simon M. F.; Biederer, Jürgen; Weinheimer, Oliver; Eichinger, Monika; Vogelmeier, Claus F.; Jörres, Rudolf A.; Kauczor, Hans-Ulrich; Heußel, Claus Peter; Jobst, Bertram; et al. (European radiology, 2025)
This multicenter trial was conducted to evaluate MRI for the longitudinal management of incidental pulmonary nodules in heavy smokers.